Calreticulin Expression Controls Cellular Redox, Stemness, and Radiosensitivity to Function as a Novel Adjuvant for Radiotherapy in Neuroblastoma. (6th January 2023) - Chen, Chih-Jung; Hu, Ya-Chuan; Chien, Yueh; Huang, Wei-Chieh; Wu, Chi-Sheng; Tsai, Chung-Ying; Lin, Yang-Hsiang; Lee, Meng-Shiue; Chien, Chian-Shiu; Yang, Yi-Ping; Lee, Meng-Chou; Tseng, Chung-Chih; et al.
Abstract : Radiotherapy (RT) is currently only used in children with high-risk neuroblastoma (NB) due to concerns of long-term side effects as well as lack of effective adjuvant. Calreticulin (CALR) has served distinct physiological roles in cancer malignancies; nonetheless, impact of radiation on chaperones and molecular roles they play remains largely unknown. In present study, we systemically analyzed correlation between CALR and NB cells of different malignancies to investigate potential role of CALR in mediating radioresistance of NB. Our data revealed that more malignant NB cells are correlated to lower CALR expression, greater radioresistance, and elevated stemness as indicated by colony- and neurospheroid-forming abilities and vice versa. Of note, manipulating CALR expression in NB cells of varying endogenous CALR expression manifested changes in not only stemness but also radioresistant properties of those NB cells. Further, CALR overexpression resulted in greatly enhanced ROS and led to increased secretion of proinflammatory cytokines. Importantly, growth of NB tumors was significantly hampered by CALR overexpression and was synergistically ablated when RT was also administered. Collectively, our current study unraveled a new notion of utilizing CALR expression in malignant NB to diminish cancer stemness and mitigate radioresistance to achieve favorable therapeutic outcome for NB.